MRI Caudate and Cingulate Volumetric Changes Related to ADHD Treatment - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Caudate and anterior cingulate cortex (ACC) volumes, measured by structural MRI, were compared in children with ADHD, previously treated and untreated, and controls, in a study at the University of Texas, San Antonio and Austin; and researchers from the UK and Canada.